A telomere-to-telomere chromosome-scale genome assembly of glass catfish (Kryptopterus vitreolus) - Chao Bian; Dahong Li; Yiluan Wang; Zhe He; Wei-Ting Chen; Cheong-Meng Chong; Hongling Zhou; Qiong Shi (Scientific Data)
Abstract Glass catfish (Kryptopterus vitreolus) is commonly distributed in several Asian countries, such as Thailand, Malaysia, and Indonesia. It is renowned for its near-transparent appearance, which has drawn considerable attention for biomedical research and the tropical ornamental fish industry. Here, we successfully constructed the first telomere-to-telomere (T2T) chromosome-scale genome assembly for glass catfish, by integration of PacBio HiFi, Nanopore ONT ultra-long, and Hi-C sequencing technologies. The haplotypic assembly covers approximately 687.7 Mb in length, featuring a high contig N50 of 21.3 Mb. This assembly was then anchored into 32 chromosomes, presenting a complete set of 64 telomeres and 32 centromeres. It was predicted with 252.4 Mb of repetitive sequences and annotated with a total of 24,696 protein-coding genes. Subsequent BUSCO analysis revealed high genome completeness (up to 96.4%). This high-quality T2T genome assembly not only provides a valuable genetic resource for investigating the molecular mechanisms underlying transparency, but also supports in-depth studies on functional genomics, genetic diversity, and selective breeding for this economically important fish species.